Migration as a Literary Dialogue Between Jorge Amado and Sandra Cisneros - Borjas de Xena, Leslie (2026)
This study provides a comparative interpretation of migration in two novels that constitute the corpus of analysis: Gabriela, clove and cinnamon (1958) by Jorge Amado and Caramelo (2002) by Sandra Cisneros. The research is framed within the constructivist paradigm with a phenomenological–hermeneutic approach, which enables the examination of migration as a historical, cultural, and subjective experience. The methodological framework draws on Paul Ricoeur’s hermeneutics, conceived as the art of textual interpretation, which is particularly relevant for analysing literary discourse expressed through symbolism, and cultural representation. The findings show that the comparative reading of both works illuminates migration as a complex phenomenon rooted in traditions, customs, and collective memories, as reimagined in the authors narratives. The protagonists emerge as migratory subjects and social actors, whose experiences reflect tensions between identity, displacement, and belonging, thus contributing to the understanding of migration in Latin American and Chicano literature